Organizacja obiegu dokumentów księgowych a operacyjne zarządzanie przedsiębiorstwem - Chojnacka, Anna (Impact of the Organization of the Flow of Accounting Documents on Operational Management of the Business Entity, 2007)
The purpose of the article is to present the role of efficient flow of accounting documents for management, in particular for the speed of decision-making process in the area of finance. Additionally the article is focused on the IT technologies supporting more efficient flow of documents of that kind in a business entity. In order to picture the abovementioned problem the example of functioning of well-organized flow of accounting documents is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 297-305